INTERPRETASI ANALISIS AMMI DENGAN BIPLOT (Kasus Analisis Interaksi Genotip Tanaman Padi dengan Lingkungan pada Percobaan Lokasi Ganda): Universitas Terbuka - Endang Wahyuningrum (LPPM Universitas Terbuka, 2003)
Multilocationtrials play an important role in agronomic research. Theseare often used to analyse the adaptability of genotypes indifferent environments. Multilocation trials also are usedto find out which environment is the best location to adaptfor each genotype that is the highest yielding in the environmentand to determine the pattern of response of genotypes acrossenvironments. ANOVA is used to compute genotype and environmentadditive effects. However, it cannot be used to analyse agenotype-environmental interaction. Principle component analysis(PCA) is only used to analyse non additive interaction effects.The statistical analysis recommended here combines the Anovawith PCA that is Additive Main effects and MultiplicativeInteraction (AMMI) with PCA. It begins with the usual analysisof variance to compute genotype and environment additive effects,and then applies PCA to analyse non additive interaction effects.The results of AMMI analysis is presented graphically in theform of biplots. The use of these procedure is exemplifiedusing secondary data set of the mean yield of padi from TheCenter of Indonesian Padi Research in Sukamandi.